UMP E-Saman by using QR code system - Ahmad Safuan, Mohamed Ramli (2019)
The Quick Response code (QR code) was first invented in 1994. Since then, it has been used as an identification mark for all kinds of commercial products, advertisements, and other public announcements. The QR code is used to provide immediate direction to the specific content. It is very simple to produce the QR code, print it or upload on the website. An editor can add simple information to a website by using a QR code-producing program. By then, the QR code is produced. QR code is very stable; it can be used for a long time without losing its quality. For now there are some issues regarding the use of sticker in UMP. Which is the user of vehicles copy the sticker from another. Second, they just edit and create the sticker by their own. Last, there probably some mistake by security officers and staff during writing the summons or entering the data. Thus, an idea to develop UMP E-Saman by using QR system to smoothen the traffic and security systems has been proposed. The objective of developing this system are, to investigate how UMP security staff authenticate registration sticker for vehicle. Then to design a system for authentication of the sticker and producing summon. Lastly, to develop UMP E-Saman by using QR code system.